2006
DOI: 10.1002/mrd.20494
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for triglyceride as an energy source during bovine oocyte maturation and early embryo development

Abstract: The potential role of endogenous triglyceride in bovine oocyte maturation and preimplantation development has been investigated. Bovine immature oocytes were recovered from abattoir-derived ovaries, matured and fertilised in vitro and the zygotes grown to the blastocyst stage in SOFaaBSA. Methyl palmoxirate (MP) blocks the oxidation of fatty acids by inhibiting mitochondrial carnitine palmitoyltransferase A. The development of zygotes exposed to MP during oocyte maturation, and of zygotes exposed to MP during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
155
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(167 citation statements)
references
References 19 publications
8
155
0
4
Order By: Relevance
“…As previous studies (Ferguson and Leese 2006) have shown that triacylglycerides can be used as an energy source in early embryonic development up to blastocyst stage, this could have contributed to the decreased fertility in heifers with retarded embryos.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…As previous studies (Ferguson and Leese 2006) have shown that triacylglycerides can be used as an energy source in early embryonic development up to blastocyst stage, this could have contributed to the decreased fertility in heifers with retarded embryos.…”
Section: Discussionmentioning
confidence: 89%
“…The production of prostaglandin F2 (PGF2) is responsible for luteolysis and prostaglandin E 2 (PGE 2 ) is involved in maternal recognition of pregnancy (Arosh et al 2002;Shelton et al 1990) and as such these pathways are of major importance in early embryonic development. Triglycerides are not only important in membrane synthesis but are also suggested to have a role in early embryonic development as an energy source (Ferguson and Leese 2006;Forde et al 2009a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e que possui, entre outros lipídeos, o ácido linoleico (ω-6) em sua composição (NORHAIZAN et al, 2013). No metabolismo animal, os UFAs são importantes no processo reprodutivo, especificamente na produção de esteroides (WANG et al, 2003), para a fluidez nas membranas plasmáticas do espermatozoide e oócito, nas mudanças no padrão de receptores de ligação (WATHES; ABAYASEKARA; AITKEN, 2007), como fonte de energia durante a maturação dos oócitos e no desenvolvimento embrionário após a implantação (FERGUSON;LEESE, 2006). O principal ácido graxo encontrado nos espermatozoides é o ácido linolênico (ω-3), sendo que o ácido docosahexaenoico (DHA), um derivado ω-3, tem importante papel na manutenção da integridade da membrana plasmática e na motilidade espermática, bem como confere maior criorresistência às células (ROBINSON et al, 2006).…”
Section: Introductionunclassified
“…Even if the lipid content of the mouse oocyte is weak (like in human), when compared to the pig and the cow, beta oxidation seems essential for meiotic resumption [5] and oocyte competence [6,7]. Its role in early pre-implantation development seems relevant in mouse [6][7][8] and bovine [9]. In terms of energy yields, one molecule of glucose forms in theory (maximum value) 38 moles of ATP for 106 ATP formed with palmitate, but with a higher formation of Reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%